Practical implications of workplace ostracism: a systematic literature review - Sheikh Sajid Mohammad; Nazir A. Nazir (Business Analyst)
Purpose – This review analyzes data from research articles published from 2010 to 2022 related to workplace ostracism which include theoretical or empirical practical implications. The primary motive of this review is to identify main themes of practical implications relevant to workplace ostracism. Design/methodology/approach – In total, 86 research articles published in 56 journals were retrieved from six well-known management science databases, namely, Science Direct, Emerald Online, Springer Link, Taylor and Francis, Wiley and Sage. The affinity diagram was utilized to organize the practical implications of the studies into meaningful themes. Moreover, in order to prioritize the main themes, the Pareto diagram was utilized. Findings – Eleven themes have been used to categorize the practical implications of the reviewed articles, demonstrating various human resource (HR) interventions for avoiding or limiting the feelings of ostracism at work. Specifically, they focus on training and development, culture, formal and informal meetings, interpersonal relationships, task interdependence, monitoring, trust and transparency, proper channel, job autonomy and individual characteristics. Originality/value – While many systematic and traditional literature reviews have been undertaken in an attempt to thoroughly organize extant literature on various aspects of workplace ostracism, no study has addressed the main themes of practical implications vis-à-vis employees experiencing workplace ostracism. Moreover, the majority of them are apparently out of date (prior to 2019), and there is just one study undertaken up to 2020.